2014
DOI: 10.1177/1535370213520108
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of endoplasmic reticulum stress in Pelizaeus-Merzbacher disease by an anti-malaria drug, chloroquine

Abstract: Pelizaeus-Merzbacher disease (PMD) is a hypomyelinating disorder caused by the duplication and missense mutations of the proteolipid protein 1 (PLP1) gene. PLP1 missense proteins accumulate in the endoplasmic reticulum (ER) of premature oligodendrocytes and induce severe ER stress followed by apoptosis of the cells. Here, we demonstrate that an anti-malaria drug, chloroquine, decreases the amount of an ER-resident mutant PLP1 containing an alanine-243 to valine (A243V) substitution, which induces severe PMD in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Chloroquine, an anti-malarial drug, was found to reduce the accumulation of the mutant PLP1 and attenuate ER stress by enhancing the phosphorylation of eIF2α (Morimura et al, 2014 ). Despite its drastic effects as an ER stress attenuator, the concentration to obtain this effect in vitro was relatively high (100 μM) for clinical application, considering its side effects.…”
Section: Implication For Potential Pmd Treatmentmentioning
confidence: 99%
“…Chloroquine, an anti-malarial drug, was found to reduce the accumulation of the mutant PLP1 and attenuate ER stress by enhancing the phosphorylation of eIF2α (Morimura et al, 2014 ). Despite its drastic effects as an ER stress attenuator, the concentration to obtain this effect in vitro was relatively high (100 μM) for clinical application, considering its side effects.…”
Section: Implication For Potential Pmd Treatmentmentioning
confidence: 99%
“…This nding reminded us of the possibility that knockdown of Rab7B recovers diseaseassociated undifferentiated states. As expected, Rab7B knockdown recovered undifferentiated morphologies induced by treatment with tunicamycin, which mimics endoplasmic reticulum (ER) stress [21,22]. It is thought that ER stress is one of the major pathological causes observed in Pelizaeus-Merzbacher disease (PMD, also called hypomyelinating leukodystrophy 1 [HLD1]) and some other neuropathies [12,23,24].…”
Section: Introductionmentioning
confidence: 55%
“…The results pertaining to the effects of Rab7B on morphological differentiation suggested the possibility that knockdown of Rab7B could help recover the inhibitory morphological differentiation in disease states [25,26]. We induced ER stress using tunicamycin [21,22] and mimicked cellular disease states, as often observed in oligodendroglial cell diseases [23,24] and many other neurological diseases [11,12]. In fact, tunicamycin inhibited morphological differentiation in a dose-dependent manner in FBD-102b cells (Figure S2).…”
Section: Knockdown Of Rab7b Recovers Tunicamycin-induced Defective Mo...mentioning
confidence: 89%
See 1 more Smart Citation
“…PLP1 encodes a protein with 276 amino acids, which is the most abundant myelin protein in the brain and can regulate myelin lamellar spacing/compaction and maintain axonal integrity via oligodendrocyte-axonal interactions [ 31 ]. Previous studies revealed that overexpression of PLP1 enhanced the accumulation of lipids in the myelin sheath, thereby promoting the progression of diseases in the central nervous system, such as Pelizaeus-Merzbacher disease [ 32 , 33 ]. Furthermore, PLP1 has the potential to inhibit the endoplasmic reticulum [ 34 ].…”
Section: Discussionmentioning
confidence: 99%